The Influence of Compensation, Perceived Supervisor Support, and Career Development on Intention to Stay with Job Satisfaction as a Mediating Variable in XYZ Manufacturing Employees - Teresia, Monika; Ardi, Ardi; Sunarjo, Richard Andre (Syntax Corporation, 2024)
This research aims to examine the company's efforts to retain competent employees in the textile industry. The research background shows that the textile industry in Indonesia has a significant contribution to the country's economy, but is faced with challenges in maintaining a competent workforce. The research was conducted at the company PT XYZ, one of the textile manufacturing companies in Tangerang. The method used is quantitative with the SEM-PLS analysis technique. Data was collected through questionnaires distributed to employees. This research aims to examine the influence of compensation, perceived supervisor support, and career development on intention to stay which is mediated by job satisfaction. The research results show that the work environment, superior behavior, career development and compensation are factors that influence employees' desire to continue working at the company. This research emphasizes the importance for organizations to create a conducive work environment, build good relationships between employees and superiors, and match the workload with the compensation received. These findings provide managerial implications for textile companies in managing human resources to maintain business sustainability and competitiveness.